Growth, productivity, input use and economics of Indian mustard as influenced by variable nitrogen doses under micro-irrigation - Rathore, S.S.; Shekhawat, Kapila; Singh, R.K. (Annals of Agricultural Research, 2018)
A field experiment was conducted on Indian mustard (Brassica juncea L. Czernj and Cosson) to evaluate the effect of variable nitrogen doses under micro-irrigation in the semi-arid conditions of Rajasthan. The experiment was laid out in spilt plot design (SPD) with three replications during winter (rabi) seasons 2010-11 and 2011-12. Irrigation through micro irrigation significantly increased seed yield by 28% over check basin. The respective increase in seed yield was 79.6%, 27.6% and 11.7% up on the application of 40, 80 and 120 kg N/ha over control during 2010-11. The respective values for 2011-12 were 64.5%, 45.5% and 28.4%. The photosynthetic rate due to various irrigation and fertigation treatments varied from 8.0 to 13.3 during 2010-11 and from 8.5 to 15.5 during 2011- 12. The production efficiency obtained under micro-sprinkler was 19.6% and 44.4% higher over check basin during 2010-11 and 2011-12. The highest sal yield, physiological parameters, production efficiency, irrigation water use efficiency and profitability of Indian mustard were obtained under micro-sprinkler over check basin method. Also, all these parameters significantly increased with increasing application of N up to 120 kg/ha. Key words: Indian mustard, Irrigation water efficiency, Micro irrigation, N fertilization, Production efficiency